Representation of Family Affection in the Broken Wings Movie - Nirmala, Azizah Prada; Haryanti, Yanti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research analyzes the representation of family affection in the Broken Wings movie. This research focuses on the family relationship of the main characters, Adji and Nani. This research uses semiotic theory by identifying signs in the scene and linking them to the meaning of family affection. The method used is descriptive qualitative with primary data collection through direct observation of movie scenes and secondary data through scene documentation on scenes related to the concept of family affection. The analysis was conducted using the Roland Barthes method with connotation and denotation approaches. The data validity used is the source triangulation technique. The results obtained are the representation of family affection in the movie Wings of Broken Wings is built and realized with five categories, namely positive feelings, fulfillment of needs, efforts to make happy, providing opportunities/freedom, and self-control, all of which have been realized in Adji and Nani's family relationship even though there are still conflicts due to lack of communication and lack of openness to each other. There is also a myth about the high risk of the head of the family's job putting family harmony at risk. The myth is successfully broken by this movie by proving that the threat to family harmony is not due to the high-risk occupation of the head of the family but the harmony of the head of the family.